Organic small molecule material, preparation method thereof and application of organic small molecule material in aqueous zinc ion battery

The organic small molecule material PD-TABQ formed by using 1,10-phenanthroline-5,6-dione and 2,3,5,6-tetrade (amino)-p-benzoquinone as the positive electrode material of zinc ion battery, solved The problem of insufficient solubility and conductivity of organic electrode materials in aqueous zinc ion batteries is achieved, and high energy density and excellent cycling performance are achieved.

CN119462660APending Publication Date: 2025-02-18SHANGHAI UNIV

Patent Information

Application Number
CN202411606163.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing organic electrode materials have problems such as high solubility, poor conductivity, initial capacity and poor circulation performance in aqueous zinc ion batteries.

Method used

The organic small molecule material PD-TABQ formed by condensation of 1,10-phenanthroline-5,6-dione and 2,3,5,6-tetrahydrofuranoquinone as the positive electrode material of zinc ion battery is easy to use The preparation method obtains high energy density and excellent cycling performance.

Benefits of technology

PD-TABQ material exhibits high energy density, good cycling performance and high purity in aqueous zinc ion batteries, solving the problem of insufficient solubility and conductivity of traditional organic electrode materials and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462660A_ABST
    Figure CN119462660A_ABST
Patent Text Reader

Abstract

The invention relates to a small organic molecule material, a preparation method thereof and an application of the small organic molecule material in an aqueous zinc ion battery, and the small organic molecule material is an imine small organic molecule (PD-TABQ) formed by condensation of 1, 10-phenanthroline-5, 6-diketone and 2, 3, 5, 6-tetra (amino) p-benzoquinone. The small organic molecule is prepared by carrying out reflux reaction, washing and drying on 1, 10-phenanthroline-5, 6-diketone and 2, 3, 5, 6-tetra (amino) p-benzoquinone, and has the advantages of low solubility, good conductivity, large capacity density and good cycle performance. When the PD-TABQ positive electrode is applied to an aqueous zinc ion battery, the PD-TABQ positive electrode has the high initial capacity of 163.4 mAh g <-1 > under the current density of 0.1 Ag <-1 >. And excellent performance and application prospects are shown in the field of aqueous zinc ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aqueous zinc ion batteries, and in particular to an organic small molecule material and a preparation method thereof and application thereof in aqueous zinc ion batteries. Background Art

[0002] So far, energy and environmental issues are regarded as the key to achieving sustainable development of human society. The rapid development of the world economy is inseparable from the supply of energy. Traditional secondary batteries still have limitations as electrical energy storage devices, which are low specific energy and short life, which creates a bottleneck for their application as power sources for electronic devices. Therefore, secondary batteries need to improve their availability to meet energy needs. Organic lithium batteries have been vigorously developed, and aqueous zinc-ion batteries have also been studied as alternatives.

[0003] Aqueous zinc-ion batteries are one of the most promising systems for large-scale energy storage applications due to their high safety, low cost, environmental friendliness, and high energy density. The zinc metal anode is rich in reserves and has a high theoretical capacity (820 mA hg -1 and 5855mA hcm -1 ), low redox potential (-0.76 V compared to standard hydrogen electrode (SHE)), environmental friendliness and superior electrochemical performance have attracted considerable attention in energy storage systems. The electrode material of the battery is the key to its performance, and the positive electrode material has a great influence on the energy density and cycle life. The use of many inorganic materials has been reported in the past few decades, but compared with them, organic matter has been proved to be a promising candidate electrode due to its variety, adjustable structure, sustainability, relatively low cost and environmental friendliness.

[0004] For example, patent CN118239954A discloses an organic positive electrode material, preparation method and application of zinc ion battery; the organic positive electrode material of zinc ion battery provided in the application is a large conjugated molecule formed by dehydration of tetraaminobenzoquinone and o-diaminonaphthoquinone and their derivatives; the organic positive electrode material improves the specific capacity by designing a large conjugated structure formed by a multi-electron center and a carbonyl group on a benzene ring and a conjugated imine; it has been verified that at 0.1A g -1 At a current density of 1000A g, the specific capacity per cycle is increased by 50% to 100% compared with the existing technology. -1 The current densities of 400, 360, 316, 280, 216 and 97 mAh g were obtained respectively. -1 The high discharge capacity is -1 When the discharge capacity reaches 350mAh g -1 But compared with the initial 0.1A g-1 This indicates that the electrode material undergoes significant irreversible changes at low current density, so its reversibility is poor.

[0005] Patent CN112961163B provides a high-capacity metal ion battery organic electrode material, a preparation method and an application thereof. The metal ion battery organic electrode material is an organic conjugated compound containing hexaazabenzene and quinone functional groups. The organic conjugated compound contains multiple redox active sites and has a theoretical capacity of more than 500 mAh g -1 The conjugated organic electrode material is obtained by dehydrating and condensing a 2,3-diamino-quinone compound and cyclohexanehexanone; when the conjugated organic electrode material is used as an aqueous zinc ion battery, it achieves a high specific capacity output and excellent cycle stability and rate performance, and the battery has a high specific capacity of 100 mA g -1 The capacity is as high as 430 mAh g at a current density of -1 ; The conjugated organic material designed by this invention solves the technical problems of low capacity and poor rate performance of existing organic materials as electrode materials for zinc ion batteries, and is expected to be used in the field of next-generation environmentally friendly, high-energy-density energy storage batteries. The synthesis of organic materials in patent CN112961163B is more complicated than the synthesis of PD-TAPB. The organic material in patent CN112961163B only uses Zn(ClO 4 ) 2 As electrolyte, this patent uses 2MZnSO 4 、3.5MZn(ClO 4 ) 2 、2MZn(CF 3 SO 3 ) 2 As electrolyte.

[0006] Patent CN114628654B provides a polyimide / polyaniline composite zinc ion battery positive electrode material and a preparation method thereof, comprising the following steps: (1) adding a mixture of aniline and phytic acid into water to obtain solution A, adding an oxidant solution into solution A, standing for reaction to obtain a polyaniline hydrogel, washing and drying to obtain a polyaniline powder; (2) dissolving perylenetetracarboxylic dianhydride and urea in an organic solvent to obtain a polyamic acid solution, adding the polyaniline powder into the polyamic acid solution, stirring evenly and then precipitating the polyamic acid-polyaniline composite with alcohol; (3) drying the polyamic acid-polyaniline composite and subjecting it to dehydration treatment to obtain a polyimide-polyaniline composite zinc ion battery positive electrode material; as a zinc ion battery positive electrode material, the invented material can exert the synergistic zinc storage effect of polyimide and polyaniline, thereby obtaining enhanced electrochemical energy storage characteristics. The positive electrode material in patent CN114628654B did not test its cycling performance, and polyimide is an electronic insulator and has poor conductivity compared to the organic small molecule PD-TAPB.

[0007] However, organic electrode materials also have some disadvantages, such as high solubility, poor conductivity, poor initial capacity and cycle performance. Therefore, researchers need to take new measures to improve these problems. Summary of the invention

[0008] In order to solve the defects of high solubility, poor conductivity, poor initial capacity and poor cycle performance of organic electrode materials, the purpose of the present invention is to provide an organic small molecule material and its preparation method and application in aqueous zinc ion batteries. The organic small molecule material (PD-TABQ) provided by the present invention is used as a positive electrode material for zinc ion batteries, showing high energy density, excellent performance and application prospects.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] One of the technical solutions of the present invention provides an organic small molecule material, wherein the structural formula of the structural unit of the organic small molecule material is as follows:

[0011]

[0012] The second technical solution of the present invention provides a method for preparing the above-mentioned organic small molecule material (PD-TABQ), wherein the organic small molecule material is formed by condensation of 1,10-phenanthroline-5,6-dione and 2,3,5,6-tetrakis(amino)-p-benzoquinone, comprising the following steps:

[0013] S1: 1,10-phenanthroline-5,6-dione, 2,3,5,6-tetrakis(amino)-p-benzoquinone and a solvent are mixed, and a product is synthesized by a reflux method under an inert gas atmosphere;

[0014] S2: The product obtained in step S1 is cooled to room temperature and then filtered, then washed and filtered multiple times, and dried to obtain the organic small molecule material PD-TABQ.

[0015] Furthermore, the solvent in step S1 is an ethanol / acetic acid mixed solution, and the volume ratio of acetic acid to ethanol in the mixed solution is (0.9-1.1):(0.9-1.1).

[0016] Furthermore, the amount of 1,10-phenanthroline-5,6-dione, 2,3,5,6-tetrakis(amino)benzoquinone and solvent in step S1 is in the following relationship: (1-2) mmol: 0.5 mmol: (9.5-10.5) mL.

[0017] Furthermore, the inert gas in step S1 is any one of argon, nitrogen and helium, preferably argon.

[0018] Furthermore, the reflux method in step S1 is performed at 78 to 80° C. for 23 to 25 hours.

[0019] Furthermore, the washing and filtering in step S2 refers to: washing with hot acetic acid, deionized water and ethanol for several times in sequence, and filtering the residual liquid of hot acetic acid, deionized water and ethanol cleanly.

[0020] Furthermore, the drying conditions in step S2 are 60-80° C. and vacuum drying for 12-36 hours.

[0021] The third technical solution of the present invention provides the application of the organic small molecule material (PD-TABQ) in the field of aqueous zinc ion batteries, and the organic small molecule material (PD-TABQ) is used as the positive electrode material of the aqueous zinc ion battery.

[0022] A fourth technical solution of the present invention provides an aqueous zinc ion battery, which includes a positive electrode material, a negative electrode material and an electrolyte, wherein the positive electrode material is the above-mentioned organic small molecule material (PD-TABQ).

[0023] The negative electrode material is: metal zinc;

[0024] The electrolyte is: ZnSO 4 、Zn(ClO 4 ) 2 or Zn(CF 3 SO 3 ) 2 Any one of the above, wherein the concentration of the electrolyte is 2 to 3.5M.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The preparation method of the organic small molecule provided by the present invention is simple to operate, feasible to implement, has low equipment requirements, and supports large-scale production.

[0027] (2) The organic small molecules synthesized by the present invention have high yield and high purity, which solves the defects of high solubility and poor conductivity of organic electrode materials.

[0028] (3) The organic small molecule material prepared by the present invention shows excellent performance and application prospects in the field of aqueous zinc ion batteries, and has good cycle performance. It shows that it has broad application prospects in the field of aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the organic small molecule (PD-TABQ) of the present invention;

[0030] Figure 2 Fourier infrared images of PD, TABQ, and PD-TABQ of the present invention;

[0031] Figure 3 is the X-ray diffraction pattern of PD-TABQ of the present invention;

[0032] Figure 4 For 2M ZnSO 4 Solubility of PD, TABQ, and PD-TABQ in electrolyte at different times;

[0033] Figure 5 2M ZnSO 4 Zn / / PD, Zn / / TABQ, and Zn / / PD-TABQ batteries with electrolyte at 0.1A g -1 Cycle life under

[0034] Figure 6 For 3.5M Zn(ClO 4 ) 2 Zn / / PD, Zn / / TABQ, Zn / / PD-TABQ batteries with electrolyte at 0.1Ag -1 Cycle life under

[0035] Figure 7 2M Zn(CF 3 SO 3 ) 2 Zn / / PD, Zn / / TABQ, Zn / / PD-TABQ batteries with electrolyte at 0.1Ag -1 Cycle life under

[0036] Figure 8 These are the EIS curves of PD, TABQ, and PD-TABQ electrodes. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0038] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0039] Example 1 An organic small molecule material

[0040] This embodiment provides an organic small molecule material, and the preparation method thereof is as follows:

[0041] S1: 1 mmol of 1,10-phenanthroline-5,6-dione, 0.5 mmol of 2,3,5,6-tetra(amino)-p-benzoquinone and 10 mL of a 1:1 ethanol / acetic acid mixed solution were added into a 250 mL round-bottom flask; the system was refluxed at 80° C. in an Ar atmosphere for 24 hours to obtain a product;

[0042] S2: After cooling the product obtained in step S1 to room temperature, filter it and wash it several times with hot acetic acid, deionized water and ethanol, and then filter out the remaining hot acetic acid, deionized water and ethanol; finally, vacuum dry it at 80°C for 12 hours.

[0043] Wherein, the structural formula of the monomer used in step S1 is:

[0044] 1,10-Phenanthroline-5,6-dione:

[0045]

[0046] 2,3,5,6-Tetra(amino)benzoquinone:

[0047]

[0048] The structural unit of the final synthesized PD-TABQ is:

[0049]

[0050] The physical and chemical properties of the imine organic small molecule PD-TABQ prepared in Example 1 were characterized. Figures 1 to 3 As shown:

[0051] The scanning electron microscopy results are as follows Figure 1 As shown, PD-TABQ has a block-like morphology.

[0052] like Figure 2 As shown in the Fourier transform infrared (FTIR) spectrum, PD-TABQ showed a group C=N (1577.67 cm -1 、1514.50cm -1 ), which is the characteristic group marked in red in the structure diagram, proving the successful synthesis of PD-TABQ.

[0053] like Figure 3 As shown, the X-ray diffraction (XRD) spectrum peaks appear at 10.7°, 18.14°, 19.62°, 21.4°, 23.4°, and 27.18°, respectively. The X-ray diffraction pattern shows that the small molecule compound has certain crystallinity.

[0054] like Figure 4 As shown in the figure, PD, TABQ, and PD-TABQ powder materials were tested in 2M ZnSO 4 Solubility in electrolyte. Monomer PD and TABQ showed severe dissolution, while PD-TABQ powder material showed almost no dissolution, which demonstrated the stability and availability of PD-TABQ in aqueous electrolyte.

[0055] Example 2 A Zn / / PD-TABQ battery (2M ZnSO 4 As electrolyte)

[0056] This example uses the imide organic small molecule PD-TABQ prepared in Example 1 as the positive electrode material, Zn as the negative electrode material, and 2M ZnSO 4 As the electrolyte, a Zn / / PD-TABQ zinc ion battery was prepared, and the specific steps included:

[0057] The organic positive electrode material PD-TABQ, conductive additives and adhesive are evenly dispersed in a solvent in a mass ratio of 5:4:1, coated on a current collector, and then vacuum dried (drying temperature is 60°C, vacuum pressure is 0.1MPa) to form an electrode film; metallic zinc is used as the negative electrode, the positive and negative electrodes are separated by a separator, and an electrolyte is injected to assemble a zinc ion secondary battery.

[0058] The conductive additive is Ketjen black, or a mixture of the above conductive materials (i.e., a mixture of organic positive electrode material PD-TABQ, conductive additive and adhesive in a mass ratio of 5:4:1); the adhesive is PVDF (polyvinylidene fluoride); the solvent is N-methylpyrrolidone; the amount of the solvent is appropriate to ensure that the organic positive electrode material PD-TABQ, the conductive additive and the adhesive are completely dissolved and then coated on the stainless steel. The current collector is stainless steel foil; the separator is glass fiber; the electrolyte is 2M ZnSO 4 .

[0059] Example 3 A Zn / / PD-TABQ battery (3.5M Zn(ClO 4 ) 2 As electrolyte)

[0060] This example uses the imide organic small molecule PD-TABQ prepared in Example 1 as the positive electrode material, Zn as the negative electrode material, and 3.5M Zn(ClO 4 ) 2 As the electrolyte, a Zn / / PD-TABQ battery was prepared, and the specific steps were the same as those in Example 2.

[0061] Example 4 A Zn / / PD-TABQ battery (2M Zn(CF 3 SO 3 ) 2 As electrolyte)

[0062] This example uses the imide organic small molecule PD-TABQ prepared in Example 1 as the positive electrode material, Zn as the negative electrode material, and 2M Zn(CF 3 SO 3 ) 2 As the electrolyte, a Zn / / PD-TABQ battery was prepared, and the specific steps were the same as those in Example 2.

[0063] Comparative Examples 1 to 3: A Zn / / PD battery

[0064] 2M ZnSO 4 、3.5M Zn(ClO 4 ) 2 、2M Zn(CF 3 SO 3 ) 2 As the electrolyte, a Zn / / PD-TABQ battery was prepared, and the specific steps were the same as those in Example 2.

[0065] Comparative Examples 4 to 6: Zn / / TABQ battery

[0066] 2M ZnSO4 、3.5M Zn(ClO 4 ) 2 、2M Zn(CF 3 SO 3 ) 2 As the electrolyte, a Zn / / PD-TABQ battery was prepared, and the specific steps were the same as those in Example 2.

[0067] Example 5 Testing of battery cycle performance

[0068] The Zn / / PD-TABQ cells prepared in Examples 2, 3 and 4 were heated to 0.1 Ag. -1 The cycle performance test was carried out under Figures 5 to 7 As shown:

[0069] Specific steps of cycle performance test:

[0070] After assembling the button cell (i.e. the above-mentioned Zn / / PD-TABQ cell), the cell was left to stand for about 6 hours to allow the electrolyte to fully moisten, and then the cell was installed on the LND-CT2001 instrument for charge and discharge cycle electrochemical testing. The voltage window of the aqueous zinc ion cell is 0.1-1.2V.

[0071] like Figure 5 As shown in the figure, the cycling performance of Zn / / PD, Zn / / TABQ and Zn / / PD-TABQ batteries were tested at 0.1Ag-1. Zn / / PD-TABQ battery uses 2M ZnSO 4 For electrolyte at 0.1A g -1 The current density is 163.4 mAh g -1 After 200 cycles, the battery capacity dropped to 67 mAh g -1 , and the coulombic efficiency is almost 100%. Zn / / PD and Zn / / TABQ use 2M ZnSO 4 For electrolyte at 0.1Ag -1 The current density is only 33.9 mAh g -1 、69.2mAh g -1 After 200 cycles, the battery capacity dropped to almost 0. As described above, the performance of Zn / / PD-TABQ is better.

[0072] like Figure 6 As shown in the figure, the cycling performance of Zn / / PD, Zn / / TABQ, and TABQZn / / PD-TABQ batteries were tested at 0.1Ag-1. The Zn / / PD-TABQ battery uses 3.5M Zn(ClO 4 ) 2For electrolyte at 0.1Ag -1 The current density is 110 mAh g -1 The initial capacity of Zn / / PD and Zn / / TABQ is high and the coulombic efficiency is almost 100%. 4 ) 2 For electrolyte at 0.1Ag -1 The current density is only 43.6 mAh g -1 、70mA hg -1 After 200 cycles, the battery capacity dropped to 13.3 mAh g -1 , 1mAh g -1 As described above, the performance of Zn / / PD-TABQ is better.

[0073] like Figure 7 As shown, at 0.1Ag -1 The cycling performance of Zn / / PD, Zn / / TABQ, and TABQZn / / PD-TABQ batteries were tested. 3 SO 3 ) 2 For electrolyte at 0.1Ag -1 The current density is 125 mAh g -1 The battery capacity dropped to 33 mAh g after 200 cycles. -1 . Zn / / PD, Zn / / TABQ use 2MZn(CF 3 SO 3 ) 2 For electrolyte at 0.1Ag -1 The current density is only 21mA hg -1 、11.9mA hg -1 After 200 cycles, the battery capacity dropped to 9.3 mAh g -1 、8.1mAhg -1 As described above, the performance of Zn / / PD-TABQ is better.

[0074] Example 6 Conductivity Test

[0075] The conductivity of the Zn / / PD-TABQ battery, Zn / / TABQ, and Zn / / PD prepared in the above examples and comparative examples was tested; 2M ZnSO 4 As electrolyte;

[0076] like Figure 8As shown in the EIS graph, it can be observed that the PD-TABQ electrode has the smallest Rct value among the three electrodes. The Rct value is usually related to factors such as electrode materials, electrolytes, electrode surface states, and the concentration of reactive species. A smaller Rct value indicates that the charge transfer process is easier to carry out, and electrons can pass through the electrode and electrolyte interface more quickly, thereby improving the rate and efficiency of the battery or electrode reaction. This shows that the PD-TABQ electrode has the best conductivity in aqueous zinc ion batteries compared to monomer small molecule electrodes.

[0077] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An organic small molecule material, characterized in that: The structural formula of the organic small molecule material is as follows:

2. A method for preparing an organic small molecule material as claimed in claim 1, characterized in that: The organic small molecule material is formed by condensing 1,10-phenanthroline-5,6-dione and 2,3,5,6-tetrakis(amino)-p-benzoquinone, and specifically comprises the following steps: S1: 1,10-phenanthroline-5,6-dione, 2,3,5,6-tetrakis(amino)-p-benzoquinone and a solvent are mixed, and a product is synthesized by a reflux method under an inert gas atmosphere; S2: The product obtained in step S1 is cooled to room temperature and then filtered, then washed and filtered multiple times, and dried to obtain the organic small molecule material.

3. The method for preparing an organic small molecule material according to claim 2, characterized in that: The solvent in step S1 is an ethanol / acetic acid mixed solution, and the volume ratio of acetic acid to ethanol in the mixed solution is (0.9-1.1):(0.9-1.1).

4. The method for preparing an organic small molecule material according to claim 2, characterized in that: The amount of 1,10-phenanthroline-5,6-dione, 2,3,5,6-tetra(amino)benzoquinone and solvent used in step S1 is in the following relationship: (1-2) mmol: 0.5 mmol: (9.5-10.5) mL.

5. The method for preparing an organic small molecule material according to claim 2, characterized in that: The inert gas in step S1 is any one of argon, nitrogen and helium.

6. The method for preparing an organic small molecule material according to claim 2, characterized in that: The reflux method in step S1 is performed at 78-80° C. for 23-25 ​​hours.

7. The method for preparing an organic small molecule material according to claim 2, characterized in that: The washing and filtering in step S2 refers to: washing with hot acetic acid, deionized water and ethanol for several times in sequence, and filtering the residual liquid of hot acetic acid, deionized water and ethanol cleanly.

8. The method for preparing an organic small molecule material according to claim 2, characterized in that: The drying conditions in step S2 are 60-80° C. and vacuum drying for 12-36 hours.

9. The use of an organic small molecule material in the field of aqueous zinc ion batteries according to claim 1, characterized in that: The organic small molecule material is used as the positive electrode material of the aqueous zinc ion battery.

10. An aqueous zinc ion battery, characterized in that: It includes a positive electrode material, a negative electrode material and an electrolyte, wherein the positive electrode material is the organic small molecule material PD-TABQ according to claim 1; the negative electrode material is: metallic zinc; the electrolyte is any one of ZnSO4, Zn(ClO4)2 or Zn(CF3SO3)2, and the concentration of the electrolyte is 2 to 3.5M.

Citation Information

Patent Citations

  • High-capacity metal ion battery organic electrode material, and preparation method and application thereof

    CN112961163A

  • Organic positive electrode material of zinc ion battery as well as preparation method and application of organic positive electrode material

    CN118239954A

  • Apparatus for measuring thickness and collecting battery gas of bettery cell

    KR102654390B1

Cited By

  • Preparation of TABQ-DHBQ electrode material and application of TABQ-DHBQ electrode material in aqueous battery

    CN120895636A